Analisis Prioritas Pengembangan Kampung Wisata Pada Pinggiran Sungai di Kota Banjarmasin - Maulana, Rizky; Maulina, Dessy (PPJP ULM, 2024)
Banjarmasin City has the potential for development of a tourist village on the riverbank. Development of tourism villages need a lot of budget with limited government budget, then prioritization is needed. Therefore, the purpose of this research is to identify criteria and alternative options for prioritizing the development of tourist villages on the riverbank in Banjarmasin City. The research respondents are 7 people considered experts and relevant to research, especially related to the research location, green villages, blue villages, and sasirangan villages by using data analysis AHP (Analytical Hierarchy Process). The results show the most dominant criteria to support the development of tourist villages on riverbanks in Banjarmasin City are attractiveness criteria with preference of 46.6%, facilities and infrastructure criteria 27.7%, accessibility criteria 16.1%, and tourism promotion criteria 9.6%. From the 3 (three) alternative in this research, the alternative of sasirangan village has the highest preference of 49.9%, green village 26.9% and blue village 23.2%. Therefore, the priority of tourism village development on the riverbank in Banjarmasin City is prioritised on sasirangan village.